Enhancing economic sustainability through entrepreneurial alertness as a mediator between innovativeness, proactive personality, and entrepreneurial intention among undergraduate students - Obinna O. Ike; Emmanuel I. Okwuchukwu; Doris C. Eyisi (Discover Psychology)
Abstract Background Entrepreneurship has emerged as a viable solution for various economic and social challenges. Understanding the inherent factors involved in the entrepreneurial process is crucial to advancing entrepreneurship. This study examines the mediating role of entrepreneurial alertness in the relationship between innovativeness, proactive personality, and entrepreneurial intention among undergraduate students. Methods A total of 1657 undergraduates (male = 976; female = 681) were recruited from different universities in southeast Nigeria using snowball sampling. The age of the participants ranged from 17 to 30 years (mean age = 21.97; SD = 3.14). Self-reported measures of the Entrepreneurial Intention Questionnaire, Individual Innovativeness Scale, Proactive Personality Scale, and Entrepreneurial Alert Scale were used for the data collection. The Hayes Process Macro for SPSS Model 4, version 26 was used for data analysis. Findings The results showed that innovativeness, proactive personality, and entrepreneurial alertness were positively associated with entrepreneurial intention respectively. In addition, entrepreneurial alertness significantly mediated the relationship between proactive personality and entrepreneurial intention among undergraduate, but did not on innovativeness. This demonstrates the interplay between endogenous and exogenous factors that affect intention behavior. Conclusion The findings of this study suggest that innovative and proactive students who are alert to entrepreneurial opportunities are more likely to possess cognitive abilities, skills, and attitudes that enhance entrepreneurial intention. This underscores the importance of cultivating traits such as innovativeness and a proactive personality, along with enhancing entrepreneurial alertness, to strengthen entrepreneurial intention among youth. This approach fosters a new generation of entrepreneurs who are capable of driving economic growth, resilience, and sustainability through opportunity recognition, innovation, and self-employment.